2022
DOI: 10.1093/ijnp/pyac013
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Transcutaneous Vagus Nerve Stimulation Diminishes Alpha-Band–Related Inhibitory Gating Processes During Conflict Monitoring in Frontal Cortices

Abstract: Background Pursuing goals is compromised when being confronted with interfering information. In such situations conflict monitoring is important. Theoretical considerations on the neurobiology of response selection and control suggest that auricular transcutaneous vagus nerve stimulation (atVNS) should modulate conflict monitoring. However, the neurophysiological-functional neuroanatomical underpinnings are still not understood. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…Moreover, alpha oscillations have been linked to mechanisms underlying IC, such as the suppression of irrelevant or interfering information ( Vaden et al, 2012 ). Our findings also support work showing a stronger power of frontal and central alpha oscillations when performance in inhibition tasks increases, via top-down inhibitory strategic processes ( Hwang et al, 2016 ; Konjusha et al, 2022 ). Additionally, our findings on the change in alpha oscillations support reports that tVNS can activate endogenous neuromodulatory signaling, such as LC-NE activity, which is correlated with increased arousal ( Sharon et al, 2021 ); this, in turn, improves the ability to overcome the interfering effects of irrelevant information in the prefrontal cortices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, alpha oscillations have been linked to mechanisms underlying IC, such as the suppression of irrelevant or interfering information ( Vaden et al, 2012 ). Our findings also support work showing a stronger power of frontal and central alpha oscillations when performance in inhibition tasks increases, via top-down inhibitory strategic processes ( Hwang et al, 2016 ; Konjusha et al, 2022 ). Additionally, our findings on the change in alpha oscillations support reports that tVNS can activate endogenous neuromodulatory signaling, such as LC-NE activity, which is correlated with increased arousal ( Sharon et al, 2021 ); this, in turn, improves the ability to overcome the interfering effects of irrelevant information in the prefrontal cortices.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have proposed that there exists an alpha-associated inhibitory gating process for interfering information in the frontal cortices. An increase in alpha activity may reflect inhibitory gating processes, whereby increased alpha power-blocking oscillation activity could block interfering or irrelevant signals to improve information processing efficiency and strengthen the dynamic functional responsiveness of brain networks ( Konjusha et al, 2022 ). In cognitive control paradigms such as the SST or the go/no-go task, response inhibition after a stop signal or no-go stimulus has been associated with increased alpha power ( Schmiedt-Fehr et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 12 studies measured the ERPs induced by taVNS using different types of tasks. The most common activity used to detect the ERPs was the Oddball task [ 40 , 42 , 43 ], and cognitive conflict resolution tasks [ 28 , 31 , 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ricci et al [48] found no effect of long-term taVNS on alpha power, also with a limited sample size (n=8). To further complicate matters, Konjusha et al [49] reported that long-term taVNS in healthy participants modulated alpha power, but in a location-dependent manner: taVNS increased alpha activity over superior parietal regions, but attenuated alpha over middle and superior frontal regions. Finally, Chen et al [50] found that long-term taVNS attenuated alpha power, but only in the higher alpha-frequency range (~11 Hz) and in an eyes-closed (but not eyes-open) condition.…”
Section: Discussionmentioning
confidence: 99%